Effectiveness and Equity in Social Spending : The Case of Spain - Vtyurina, Svetlana (IMF Working Papers; Working Paper ;, 2020)
Spain is experiencing sustained economic and social disparities in several areas. Social spending policies have a heightened responsibility to respond but are challenged by high public debt and pressures from an aging society. This study takes stock of the level and effectiveness of public social expenditure from a cross-country and macroeconomic view, complementing recent targeted spending reviews. The results suggest that social protection spending should aim to improve redistribution through better targeting the most vulnerable while more effective education and active labor market policies should aim to create more equal opportunities and income prospects. In some areas more fiscal resources are needed. But social spending alone cannot reduce inequality, and efforts also should be directed toward making the labor market more inclusive.